Electron microscopy of Achlya deoxyribonucleic acid sequence organization. - Pellegrini, M (1981)
Electron microscopic analysis of reassociated deoxyribonucleic acid (DNA) from the aquatic fungus Achlya bisexualis revealed details of the sequence arrangement of the inverted repeats and both the highly and moderately repetitive sequence clusters. We used the gene 32 protein-ethidium bromide technique for visualizing the DNA molecules, a procedure which provides excellent contrast between single- and double-stranded DNA regions. Long (greater than 6-kilobase) DNA fragments were isolated after reannealing to two different repetitive C0t values, and the renatured structures were then visualized in an electron microscope. Our results showed that the inverted repeat sequences were short (0.5 kilobase, number-average) and separated by nonhomologous DNA of various lengths. These pairs of sequences were not clustered within the genome. Both highly repetitive and moderately repetitive DNA sequences were organized as tandem arrays of precisely paired, regularly repeating units. No permuted clusters of repeating sequences were observed, nor was there evidence of interspersion of repetitive with single-copy DNA sequences in the Achlya genome.